Reflections on the Interest in Buying Smartphone Products among Millennials: Consumer Satisfaction as the Mediating Effect - Halim, Fitria; Sibarani, Hendra Jonathan; Moktar, Brilian; Sugiat, Maria; Sudirman, Acai (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
The urgency of this study is to determine the role of consumer satisfaction as a mediating variable between product attributes and price on the purchase interest of smartphones among millennials. This study obtains the data using a survey through 240 online questionnaires with a quantitative approach. The PLS-SEM statistics are initiated with the outer model’s quality tests and the inferential statistics in the inner model. Based on data analysis on the effect of mediation, it can be seen that consumer satisfaction is not able to mediate the relationship between product attributes and purchase intention. Meanwhile, in the pattern of the relationship between price and purchase intention, it turns out that consumer satisfaction can be a mediating variable.